2019
DOI: 10.1002/mmce.21698
|View full text |Cite
|
Sign up to set email alerts
|

Study of miniaturized E‐patch antenna loaded with novel E‐shape SRR metamaterial for RFID applications

Abstract: A new design of compact micro strip antenna, based on a newly structure "E"SRR of metamaterial is proposed and designed using CST Microwave Studio. It has been found that the characteristics of new micro strip antenna with novel designed metamaterials placed in the same plane as the radiating element are comparable to the conventional patch antennas, whereas its gain, directivity, and radiating efficiency are remarkably improved. For the design and fabricated antenna, it shows that with the addition of split r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
3
1
Order By: Relevance
“…The percentage size reduction is greater than References 23‐28. Further, the frequency reduction is greater than 47% unlike the research reported in References 24 and 26.…”
Section: On‐car Performance Estimationcontrasting
confidence: 57%
See 1 more Smart Citation
“…The percentage size reduction is greater than References 23‐28. Further, the frequency reduction is greater than 47% unlike the research reported in References 24 and 26.…”
Section: On‐car Performance Estimationcontrasting
confidence: 57%
“…This reduction in operating frequency without increasing the antenna footprint is described as antenna miniaturization. The realized frequency reduction and hence the miniaturization is higher than the antennas reported in References 13‐18,22‐27.…”
Section: On‐car Performance Estimationmentioning
confidence: 75%
“…For all these structures, the maximum achievable gain is of the order of 2-6 dB in the UHF and SHF bands, which is not suitable for RFID application because the antenna, which has low performance in terms of gain and directivity, may cause tag detection errors or losses in the supply network in other applications, thus limiting the range of applications. There are numerous techniques based on metamaterials that can be employed above [28], or inside the radiating element [29][30][31]. However, only a single band has been successfully achieved around 2.4 GHz, with a maximum gain of 6 dB, at the expense of increased size.…”
Section: Introductionmentioning
confidence: 99%
“…Metamaterials employing has been a novel method to realize high performance of the antenna 8–12 . As the two‐dimensional structure, metasurface has been widely used in the antenna design 13–15 .…”
Section: Introductionmentioning
confidence: 99%